Prevention and treatment of recurrent Hepatitis B after liver transplantation: the current role of nucleoside and nucleotide analogues - Schiff Eugene R; Schreibman Ian R (BMC, 2006)
Abstract The Hepatitis B virus (HBV) is a DNA virus that can cause both acute and chronic liver disease in humans. Approximately 350-400 million people are affected worldwide and up to one million deaths occur annually from cirrhosis and hepatocellular carcinoma. When cirrhosis and liver failure develop, the definitive treatment of choice remains orthotopic liver transplantation (OLT). In the past, an unacceptable HBV recurrence rate with a high rate of graft loss was noted. The use of Hepatitis B immunoglobulin (HBIG) has resulted in improved patient and graft survival rates. The addition of the nucleoside analog Lamivudine (LAM) to HBIG has improved these survival curves to an even greater degree. Prolonged use of LAM will almost invariably lead to the development of viral mutations resistant to the drug. There are now several other nucleoside and nucleotide analogs (Adefovir, Entecavir, Tenofovir, and Truvada) available for the clinician to utilize against these resistant strains. It should be possible to prevent recurrence in most, if not all, post-transplant patients and also to significantly reduce viral loads with normalization of transaminases in those who have developed recurrent infection. The antiviral regimen should be robust and minimize the risk of breakthrough mutations. A prudent approach may be the implication of combination antiviral therapy. This review summarizes the efficacy of previous regimens utilized to prevent and treat recurrent HBV following OLT. Particular attention will be paid to the newer nucleoside and nucleotide analogs and the direction for future strategies to treat HBV in the post transplant setting.